(untitled) (Global Journal of Human-Social Science, 2013)
Women s inscription continues to engage a place of substance for more reasons than one It has questioned the accessible viewpoints which are fundamentally patriarchal All women s writing need not necessarily be feminist But feminist interpretations can appear through absence and denial The sufferings of Indian women marital discord existentialism annoyance are the major themes of feminist writing Female quest for individuality has been a pet theme for many a woman novelist After the Second World War it has become possible that women novelists of quality have become inspirational for Indian English fiction